2003
DOI: 10.1007/s12122-003-1019-9
|View full text |Cite
|
Sign up to set email alerts
|

Internal markets for department chairs: Comparative advantage, life-cycle, and jury duty

Abstract: We examine the internal market for department chairs in U.S. universities and provide the first empirical evidence concerning the determinants of departmental chair service using data from the economics departments in eight large public universities. The results reveal the wage premium for chairs increases with length of service and continues for an extended period thereafter. The chair premium largely represents compensation for foregone research and the attendant atrophy of research skills. The empirical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…It is not unusual for senior administrators to select Chairs who have either undergone a decline in research productivity or made fewer research‐specific investments over their careers (McDowell, Singell & Stater, ; McDowell, Singell & Stater, ), although it is less common in Tier 1 research universities that assign greater weight to the research productivity of potential departmental Chairs (Moore, Newman, & Turnbull. ; Ness & Samet, , Ehrenberg, ).…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…It is not unusual for senior administrators to select Chairs who have either undergone a decline in research productivity or made fewer research‐specific investments over their careers (McDowell, Singell & Stater, ; McDowell, Singell & Stater, ), although it is less common in Tier 1 research universities that assign greater weight to the research productivity of potential departmental Chairs (Moore, Newman, & Turnbull. ; Ness & Samet, , Ehrenberg, ).…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…If he or she enters, the wage increases to wa and grows at the rate h for the term of service, grows at the rate rj after the term ends until time tj> and then drops down to the wage located on the lowest line in the figure. After that, the wage grows at the rate g until the time of retirement tr2 If, instead, the economist decides not to enter administration at time td, the wage grows from the value wd at the rate g for the rest of his or her career until the time of retirement tr.3 Becoming chair at time td is thus preferred to not entering at that time if and only if the areas la-1 The assumption of slow but positive wage growth after the term of service is consistent with the finding that it takes up to a decade for the wage gain from administration to completely erode (Moore et al 2003;Saks 1977) . We also investigated the case where the wage differential continuously erodes until the post-administration wage profile meets the regular faculty profile, which yielded the prediction that knowledge depreciation has non-linear effects on both entry and exit.…”
Section: The Decision To Enter the Chairmentioning
confidence: 60%
“…The higher wages of department heads are a compensating differential not only for a task deemed as secondary by many academics, but for the depreciation of research skills and lower future wage growth that results from time spent in an administrative position (e.g., see Moore, Newman, and Turnbull 2003). Goodwin and Sauer (1995) and Ragan and Rehman (1996) both found that there is a substantial decline in research productivity during and after a term of service as department chair.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations